2015
DOI: 10.1161/circulationaha.114.012525
|View full text |Cite
|
Sign up to set email alerts
|

Propensity-Matched Comparisons of Clinical Outcomes After Transapical or Transfemoral Transcatheter Aortic Valve Replacement

Abstract: Background— The higher risk of adverse outcomes after transapical (TA) versus transfemoral (TF) transcatheter aortic valve replacement (TAVR) could be attributable to TA-TAVR being an open surgical procedure or to clinical differences between TA- and TF-TAVR patients. We compared outcomes after neutralizing patient differences using propensity score matching. Methods and Results— From April 2007 to February 2012, 1100 Placement of Aortic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
134
3
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 258 publications
(155 citation statements)
references
References 29 publications
11
134
3
3
Order By: Relevance
“…However, TA-TAVR is associated with higher mortality and prolonged recovery when compared with TF-TAVR, and unlike TF-TAVR, health-related quality of life after TA-TAVR is no better than SAVR. 19,20 Our study showed that TA-TAVR is also associated with an increased risk of 30-day readmission. This association may be influenced by residual confounding as patients undergoing TA-TAVR are typically sicker with more complex PVD that cannot be captured completely in an administrative database such as the NRD.…”
Section: Discussionmentioning
confidence: 60%
“…However, TA-TAVR is associated with higher mortality and prolonged recovery when compared with TF-TAVR, and unlike TF-TAVR, health-related quality of life after TA-TAVR is no better than SAVR. 19,20 Our study showed that TA-TAVR is also associated with an increased risk of 30-day readmission. This association may be influenced by residual confounding as patients undergoing TA-TAVR are typically sicker with more complex PVD that cannot be captured completely in an administrative database such as the NRD.…”
Section: Discussionmentioning
confidence: 60%
“…A previous study involving high-risk patients treated with TAVR also showed higher rates of adverse periprocedural events and death among propensitymatched patients who underwent transapical access than among those who underwent transfemoral access. 28 Further studies would be needed to explore the hypothesis that in intermediaterisk patients who are not candidates for TAVR with transfemoral access, TAVR with transthoracic access may have similar or worse outcomes than surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In PARTNER, unadjusted stroke risk was higher after TA-than after TF-TAVR; however, after adjusting for baseline characteristics, risk was similar. 23 Other studies and meta-analyses have shown no difference in stroke risk based on access site. 24 Risk of stroke after TAVR has decreased over time, though less pronounced in the TF group, 3,25 where evolution of the delivery system and refined patient selection may have contributed to a decrease.…”
Section: Findings In Contextmentioning
confidence: 98%